2020
DOI: 10.1111/icad.12404
|View full text |Cite
|
Sign up to set email alerts
|

Assessing zinc tolerance in two butterfly species: consequences for conservation in polluted environments

Abstract: Zinc is a widespread pollutant released from industrial combustion, automobile residue, and mining. Zinc accumulates in soils and mobilises into plant tissue where it may be consumed to potentially toxic levels by leaf feeding insects, including developing pollinators. While zinc tolerance thresholds have been previously assessed in insect pollinators, most observations are limited to model organisms and pest species. We lack understanding of zinc tolerance in insects of conservation concern. We assess dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 84 publications
0
23
2
1
Order By: Relevance
“…One potential factor influencing the abundance of the iconic Monarch butterfly could be exposure to elevated levels of heavy metals in their Milkweed foodplants where they grow along roadsides. Shephard et al (2020) found that caterpillars experimentally exposed to different levels of zinc in artificial diet had reduced survival, but at levels above those reported from roadside areas studied in the Midwestern USA. For contrast, they also studied the generalist and ubiquitous Cabbage white butterfly and observed very different (even positive) responses to elevated zinc.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…One potential factor influencing the abundance of the iconic Monarch butterfly could be exposure to elevated levels of heavy metals in their Milkweed foodplants where they grow along roadsides. Shephard et al (2020) found that caterpillars experimentally exposed to different levels of zinc in artificial diet had reduced survival, but at levels above those reported from roadside areas studied in the Midwestern USA. For contrast, they also studied the generalist and ubiquitous Cabbage white butterfly and observed very different (even positive) responses to elevated zinc.…”
mentioning
confidence: 63%
“…Shephard et al . () found that caterpillars experimentally exposed to different levels of zinc in artificial diet had reduced survival, but at levels above those reported from roadside areas studied in the Midwestern USA. For contrast, they also studied the generalist and ubiquitous Cabbage white butterfly and observed very different (even positive) responses to elevated zinc.…”
mentioning
confidence: 84%
“…Although visitation was reduced, pollinators did frequently consume even the greatest experimental concentrations of metals. Further research is needed to understand if and how this might affect them, though concentrations of Pb have been negatively related to bumblebee colony growth in urban areas (Sivakoff et al., 2020), concentrations of Cd, Pb and Zn have been linked to wild bee abundance, diversity and forewing structure (Moroń et al., 2012; Szentgyörgyi et al., 2017) and concentrations of Zn between 55 and 1,158 ppm (a similar range to that measured in road verge flowers) have been found to affect caterpillar survival and development (Shephard et al., 2020). A recent study estimated that the LC50 after 7 days for bumblebees feeding on contaminated sugar water was 0.83 ppm for Cd and 66.55 ppm for Cu (Rothman et al., 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Surveys of common milkweed collected from roadside sites across MN, USA, have shown that leaf zinc and sodium concentrations are higher in plants along busier roads and in plants closer to the road edge ( Mitchell et al , 2020 ; Shephard et al ., in review ). Prior experimental work has investigated the effects of increased dietary sodium ( Snell-Rood et al , 2014 ) and increased dietary zinc ( Shephard et al , 2020 ) on monarch development in isolation, but not yet in combination. Increased dietary sodium enhances neural and muscle development in monarchs, but can reduce survival at high levels ( Snell-Rood et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite elevated levels of sodium in roadside milkweed ( Mitchell et al , 2020 ) neither caterpillars nor ovipositing females avoid leaves with toxic sodium levels ( Mitchell et al , 2019 ). Roadside milkweed accumulates sodium to levels that are potentially toxic for monarchs, but observed levels of zinc in roadside milkweed are likely not toxic for monarchs ( Mitchell et al , 2020 ; Shephard et al , 2020 ). It remains unclear how elevated zinc affects monarch development and performance when experienced in combination with other micronutrients, such as sodium.…”
Section: Introductionmentioning
confidence: 99%